2019
DOI: 10.1007/s11869-019-00758-w
|View full text |Cite
|
Sign up to set email alerts
|

Active botanical biofiltration of air pollutants using Australian native plants

Abstract: Air pollutants are of public concern due to their adverse health effects. Biological air filters have shown great promise for the bioremediation of air pollutants. Different plant species have previously been shown to significantly influence pollutant removal capacities, although the number of species tested to date is small. The aim of this paper was to determine the pollutant removal capacity of different Australian native species for their effect on active biowall particulate matter, volatile organic compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 73 publications
(97 reference statements)
0
10
0
Order By: Relevance
“…Unfortunately, smaller particles are more damaging to human health than larger particles (WHO, 2016), reducing the benefits from plants in this regard. However, removal of pollutants from the air may be damaging to the plant, and some studies argued that the plants which are most efficient in removal would not survive long in polluted environments due to accumulation of contaminants in plant tissues (e.g., Paull et al, 2019). However, a later study by the same authors found that many species of plants exposed to urban air can withstand the polluted environment and show no signs of reduced vitality compared with non-exposed plants (Paull et al, 2021).…”
Section: Planning Of Green Roofs and Green Walls Within The City -Loc...mentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, smaller particles are more damaging to human health than larger particles (WHO, 2016), reducing the benefits from plants in this regard. However, removal of pollutants from the air may be damaging to the plant, and some studies argued that the plants which are most efficient in removal would not survive long in polluted environments due to accumulation of contaminants in plant tissues (e.g., Paull et al, 2019). However, a later study by the same authors found that many species of plants exposed to urban air can withstand the polluted environment and show no signs of reduced vitality compared with non-exposed plants (Paull et al, 2021).…”
Section: Planning Of Green Roofs and Green Walls Within The City -Loc...mentioning
confidence: 99%
“…Species traits has been shown to influence ability for air quality purification (Liu et al, 2021;Ysebaert et al, 2021). For instance, leaf morphology is an important factor in PM removal (Speak et al, 2012;Paull et al, 2019) and species with high photosynthetic capacity, stomatal conductance, and transpiration are efficient in removing all gaseous pollutants from the air (Baraldi et al, 2019). A review by Liu et al (2021) concluded that air quality purification ability is higher for intensive green roofs than for more extensive green roofs.…”
Section: Implementation Of Green Roofs and Green Walls -Design Parame...mentioning
confidence: 99%
See 1 more Smart Citation
“…In ambient conditions, this system demonstrated exponential decay for all the targeted air pollutants; however, the study indicates a requirement for in situ long-term assessment. The use of native Australian plants and their efficiencies in an ALW system was assessed; the performance of native and ornamental plants was compared (Paull et al, 2019). Single-pass removal efficiency revealed the less effective nature of the native Australian plants for the removal of PM and CO 2 when compared with the common ornamental plants.…”
Section: Active Botanical Biofiltration In Laboratory Conditionsmentioning
confidence: 99%
“…In a biofilter, the biomass mains to elimination of pollutants over time, which has been connected to growth in flow rate of air in the bed. Biomass gathering is better at the commencement segments of the biofilters, and leads to a variation in bed features e.g., decrease in inter particle void space, and the compaction of natural packing material like wood chips; these variations source for channeling and better pressure drop (Ryu et al 2010;Xi et al 2015;Paull et al 2019). In overall, there is an around linear growth in pressure drop with growing gas flow rate, which starts to develop exponential at higher flow rates.…”
Section: Introductionmentioning
confidence: 99%